Rosalind Franklin : DNA discoverer - Streissguth, Thomas, 1958- (Women in science (Essential Library (Firm)), 2018)
Highlights the life of career of scientist Rosalind Franklin, focusing on her Anglo-Jewish childhood, family background, education, personal traits, laboratory research on DNA, and technical experience.